A REVIEW ON LAWSONIA INERMIS: A POTENTIAL MEDICINAL PLANT - AL-SNAFI, ALI ESMAIL (International Journal of Current Pharmaceutical Research, 2019)
Lawsonia inermis (Family: Lythraceae) contained carbohydrates, phenolic, flavonoids, saponins, proteins, alkaloids, terpenoids, quinones, coumarins, xanthones, fat, resin and tannins. It also contained 2-hydroxy-1,4-naphthoquinone (lawsone). Many alkaloids, naphthoquinone derivatives, phenolics and flavonoids were isolated from different parts of Lawsonia inermis. The pharmacological studies showed that Lawsonia inermis showed antibacterial, antifungal, antiparasitic, molluscicidal, antioxidant, hepatoprotective, central nervous, analgesic, anti-inflammatory, antipyretic, wound and burn healing, immunomodulatory, antiurolithiatic, antidiabetic, hypolipidemic, antiulcer, antidiarrhoeal, diuretic, anticancer and many other pharmacological effects. The current review will highlight the chemical constituents and pharmacological effects of Lawsonia inermis.